Storytelling für Museen: Herausforderungen und Chancen - Kramper, Andrea (transcript, 2017)
No matter how thrilling any subject may be: The way it is presented is the decisive factor about whether it will be understood or not. Museums are faced with a fundamental dilemma: On the one hand, they must meet scientific requirements, on the other hand they have to make their contents accessible to the general public. Story-telling – a communication method that brings contents across by means of classic narrative patterns - offers a solution to this problem. Andrea Kramper illuminates the challenges and the potential of storytelling by applying new findings from the fields of museology, cognitive science and communication science, showing how museums could profit from them.